2018
DOI: 10.1063/1.5064716
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectroscopy of methyl vinyl ketone oxide: A four-carbon unsaturated Criegee intermediate from isoprene ozonolysis

Abstract: Ozonolysis of isoprene, one of the most abundant volatile organic compounds in the atmosphere, proceeds through methyl vinyl ketone oxide (MVK-oxide), methacrolein oxide, and formaldehyde oxide (CH 2 OO) Criegee intermediates. The present study focuses on MVK-oxide, a four-carbon unsaturated carbonyl oxide intermediate, using vacuum ultraviolet photoionization at 118 nm and UV-visible induced depletion of the m/z = 86 mass channel to characterize its first π * ← π electronic transition. The electronic spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
129
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(141 citation statements)
references
References 67 publications
7
129
2
Order By: Relevance
“…Barber et al (30) recently reported a scheme for the selective production of MVK-oxide and employed this method to record an IR-action spectrum. The same scheme was used by Vansco et al (31) to obtain a UV-Vis depletion spectrum, which displayed broad absorption features from 300 to 450 nm, consistent with both syn-and anti-conformers. Both studies generated MVKoxide via 248 nm photolysis of 1,3-diiodobut-2-ene in O 2 /Ar carrier gas that was sampled following supersonic expansion (T∼10 K) under collision-free conditions.…”
Section: Significancementioning
confidence: 99%
“…Barber et al (30) recently reported a scheme for the selective production of MVK-oxide and employed this method to record an IR-action spectrum. The same scheme was used by Vansco et al (31) to obtain a UV-Vis depletion spectrum, which displayed broad absorption features from 300 to 450 nm, consistent with both syn-and anti-conformers. Both studies generated MVKoxide via 248 nm photolysis of 1,3-diiodobut-2-ene in O 2 /Ar carrier gas that was sampled following supersonic expansion (T∼10 K) under collision-free conditions.…”
Section: Significancementioning
confidence: 99%
“…Both have extended conjugation involving six π electrons across the vinyl (CH 2 =C) and carbonyl oxide (C=O + -O -) functional groups. [8][9] They are 5 formation of an OH or HO 2 radical co-product. [27][28][29][30] The stable products are identified using multiplexed photoionization mass spectrometry (MPIMS) (Section IV).…”
Section: Introductionmentioning
confidence: 99%
“…distinctly different than simple saturated carbonyl oxides, such as formaldehyde oxide (CH 2 OO) and alkyl-substituted Criegee intermediates, which have four π electron systems (C=O + O -). [8][9][10][11][12][13][14][15][16] In addition, MVK-oxide and MACR-oxide each have four conformational forms with similar predicted ground state energies (within ca. 3 kcal mol -1 ).…”
mentioning
confidence: 99%
“…[32][33] Via this new synthesis scheme, recent studies have shown that the resonancestabilization would affect the reactivity and thus the atmospheric fate of MVKO. [32][33][34][35][36] For MVKO, there are four possible isomers/conformers. 2,32,[34][35] Similar to simpler CIs, the barrier of rotating the carbonyl C = O bond is high, resulting in non-interconverting syn and anti isomers (following the nomenclature of Barbar et al).…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] For MVKO, there are four possible isomers/conformers. 2,32,[34][35] Similar to simpler CIs, the barrier of rotating the carbonyl C = O bond is high, resulting in non-interconverting syn and anti isomers (following the nomenclature of Barbar et al). 32,37 However, the barrier of rotating the C─C single bond between the C = C and C = O bonds is low, giving essentially an equilibrium mixture of cis and trans conformers.…”
Section: Introductionmentioning
confidence: 99%